Controle do Alphitobius diaperinus e estudo dos parâmetros físicos e químicos em camas de aviário reaproveitadas, utilizando cal e lona na superfície - Gehring, Vandreice Salamoni (2018)
The reuse of poultry bed is a practice used to reduce costs in the production of broilers. The use of lime and the fermentation of beds, using canvas on its surface, are methods that have been employed to reduce microbial and insect contamination such as Alphitobius diaperinus. The objective of this study was to evaluate the temperature, humidity, pH, water activity, ammonia and control of the nest egg (Alphitobius diaperinus) in reutilized aviary beds, using treatments of lime and canvas on the surface during the period of 08 days. The physical-chemical parameters evaluated (moisture, temperature, ammonia, pH and water activity, did not present statistical difference between the different bed treatments used (addition of lime and fermentation with tarpaulin). However, there was no difference between the treatments with different water inclusions, and the temperatures measured in the bed did not reach critical levels for the elimination of microorganisms, ranging from 26 to 27ºC. The maximum pH level observed was 8.73, in the treatment with addition of virgin lime, however, did not reach values to occur a significant reduction microbial that is above pH 9. There was no difference between the treatments on bed wetness and water activity and both parameters were shown favorable to the development. In relation to the effect of the treatments in the control of the small cascudinhos, the treatments placing of canvas with addition of 02 and 03 liters of water and 03 liters of water plus 600 g of lime per square meter showed the elimination of 100% of insects. This result is associating the volatilization of ammonia under fermentation conditions and the potentiation of gas production when associated with lime water. The results indicate that both methods that are currently being used for bed disinfection need to be improved to ensure the elimination of major pathogenic microorganisms for poultry farming. As for the elimination of the cascudinhos, ammonia above 400ppm proved to be efficient in its control.